A New Technique for the Digitization and Restoration of Deteriorated Photographic Negatives. (21st October 2009) - Landon Landon, George V. George V.; Clarke Clarke, Duncan Duncan; Seales Seales, W. Brent W. Brent
Abstract : This work describes the development and analysis of a new image-based photonegative restoration system. Deteriorated acetate-based safety negatives are complex objects due to the separation and channeling of their multiple layers that has often occurred over 70 years time. Using single-scatter diffuse transmission model, the intrinsic intensity information and shape distortion of film can be modeled. A combination of structured-light and high-dynamic range imaging is used to acquire the data which allows for automatic photometric and geometric correction of the negatives. This is done with a simple-to-deploy and cost-effective camera and LCD system that are already available to most libraries and museums. An initial analysis is provided to show the accuracy of this method and promising results of restoration of actual negatives from a special archive collection are then produced.